Effects of whey protein plus vitamin D supplementation combined with progressive resistance training on glycaemic control, body composition, muscle function and cardiometabolic risk factors in middle‐aged and older overweight/obese adults with type 2 diabetes: A 24‐week randomized controlled trial. Issue 4 (19th January 2021) - Miller, Eliza G.; Nowson, Caryl A.; Dunstan, David W.; Kerr, Deborah A.; Menzies, David; Daly, Robin M.
Abstract: Aim: To determine the effect of whey protein plus vitamin D supplementation combined with progressive resistance training (PRT) on glycaemic control, body composition, muscle function and cardiometabolic risk factors in middle‐aged and older adults with type 2 diabetes (T2D). Materials and Methods: In this 24‐week, randomized controlled trial, 198 overweight/obese adults (aged 50–75 years) with T2D undertook PRT (2‐3 days/week) with random allocation to whey protein (20 g each morning plus 20 g postexercise) plus vitamin D3 (2000 IU/day) (PRT + ProD, n = 98) or no supplementation (PRT, n = 100). Primary outcomes were HbA1c and homeostatic model assessment‐2 of insulin resistance (HOMA2‐IR). Secondary endpoints included fasting plasma glucose (FPG), body composition, muscle strength, physical function, blood pressure, blood lipids and inflammatory markers. Results: At 24 weeks, supplementation did not enhance the effects of PRT on HbA1c (mean absolute change: PRT + ProD −0.10% [95% CI, −0.24%, 0.05%] vs. PRT −0.17% [95% CI, −0.32%, −0.03%], p = .322) or HOMA2‐IR (PRT + ProD −0.12 [95% CI, −0.27, 0.03] vs. PRT −0.03 [95% CI, −0.14, 0.09], p = .370). There were also no significant between‐group differences for the mean changes in the secondary outcomes, except that FPG improved in PRT versus PRT + ProD (net difference, 0.6 mmol/L [95% CI, 0.1, 1.0], P = .018), while interleukin IL‐10 (61% [95% CI 31%, 92%], P < .001), tumour necrosis factor‐α (16% [95% CI, 3%, 29%], p = .015) and 30‐s sit‐to‐stand performance (number, 1.0 [95% CI, −0.05, 1.5], p = .047) increased in PRT + ProD versus PRT. Conclusions: In older overweight/obese adults with T2D, daily whey protein plus vitamin D supplementation did not augment the effects of PRT on measures of glycaemic control, body composition, muscle strength or cardiometabolic risk factors.